UTILIZATION OF DIGITAL MEDIA AS A ALTERNATIVE DISTRIBUTION MEDIA FOR PYONG-PYONG - Yulio Jansen; Vincentia Ananda Arum Permatasari (Jurnal Komunikasi dan Media, 2022)
The development of communication technology that exists today has brought digital media into the global and real time distribution. No exception for music industries, the phenomenon of the emergence indie bands has driven by the use of digital media as an alternative medium for distribution and promotions. This study aims to find out how indie bands using the digital media, one of which is Pyong-pyong, which incidentally has experienced two media ages, digital media and analog media. This research is using qualitative descriptive approach, with uses and gratification theory. Using interviews, observations and documentation for data collection methods. The results has show that digital media not just an alternative, more than that digital media has become a substitute for analog media